2020
DOI: 10.1002/chem.201904948
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Current Electrolysis for the Electrocatalytic Synthesis of Mixed Disulfide via Sulfur–Sulfur Bond Metathesis towards Dynamic Disulfide Libraries

Abstract: A novel approach of electrolysis using alternating current was applied in the sulfur–sulfur bond metathesis of symmetrical disulfides towards unsymmetrical disulfides. As initially expected, a statistical distribution in disulfides was obtained. Furthermore, the influence of electrode polarisation by alternating current was investigated on a two‐disulfide matrix. The highly dynamic nature of this chemistry resulted in the creation of dynamic disulfide libraries by expansion of the matrices, consisting of up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 44 publications
1
50
0
Order By: Relevance
“…As shown, ab road spectrum of functional groups was tolerated with good to quantitative efficiency.Specifically,electron-donating groups, such as alkyl (4,5,15,16), ether (6,7,17,18), and thioether groups (9), and electron-withdrawing groups including fluoro (8, 22, 23, 25, 28, 29), chloro (2, 22, 26, 28), bromo (27), and trifluoromethoxy (10,19)m oieties reacted smoothly in the aqueous system. Interestingly,t he groups that were electrochemicaly oxidative and reductive labile were intact in moderate yields.T his observation was exemplified by the amino (20,21), and thioether groups for the electrochemical oxidative moieties and by the aldehyde (32), ketone (31), and ester (11,33)g roups for the reductive labile moieties. Regarding the steric hindrance,t he meta-substituted starting materials exclusively favored the less steric position (16,22,23,28,29).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown, ab road spectrum of functional groups was tolerated with good to quantitative efficiency.Specifically,electron-donating groups, such as alkyl (4,5,15,16), ether (6,7,17,18), and thioether groups (9), and electron-withdrawing groups including fluoro (8, 22, 23, 25, 28, 29), chloro (2, 22, 26, 28), bromo (27), and trifluoromethoxy (10,19)m oieties reacted smoothly in the aqueous system. Interestingly,t he groups that were electrochemicaly oxidative and reductive labile were intact in moderate yields.T his observation was exemplified by the amino (20,21), and thioether groups for the electrochemical oxidative moieties and by the aldehyde (32), ketone (31), and ester (11,33)g roups for the reductive labile moieties. Regarding the steric hindrance,t he meta-substituted starting materials exclusively favored the less steric position (16,22,23,28,29).…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, cross‐coupling product 66 was accompanied by two other homocoupling products 36 and 55 , in a ratio of approximately 1:1:1 when an equal molar substance was present. Furthermore, selective cross‐coupling of free radicals is highly desirable . Under standard condition B, the cross‐coupling of compound 66 could be significantly improved by simply adding 5 equivalents of one substance [Eq.…”
Section: Preliminary Mechanism Investigationmentioning
confidence: 93%
See 1 more Smart Citation
“…Notable works showed that AC can be successfully applied in the electrosynthesis of phenol, 12 trifluoromethylated arenes, 13 or in accelerating S–S bond metathesis through reversible redox steps. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Notable works showed that AC can be successfully applied in the electrosynthesis of phenol, 11 trifluoromethylated arenes, 12 or in accelerating S-S bond metathesis through reversible redox steps. 13…”
Section: Introductionmentioning
confidence: 99%